Effect of Matching Between the Adopted Corporate Response Strategy and the Type of Hypocrisy Manifestation on Consumer Behavior: Mediating Role of Negative Emotions - Wang, Zhigang; Liu, Xintao; Zhang, Lei; Wang, Chao; Liu, Rui (Frontiers in Psychology, 2022)
Consumers may sense hypocrisy in corporate social responsibility (CSR) if they note inconsistency in enterprises’ words and deeds related to CSR. This inconsistency originates from the intentional selfish actions and unintentional actions of enterprises. Studies have revealed that consumers’ perception of hypocrisy has a negative influence on enterprise operation. However, studies have not examined how corporate responses to consumers’ hypocrisy perception affect consumers’ attitude and behavior. Therefore, the present study attempted to determine the measures that should be undertaken by enterprises to reduce consumers’ negative response to them when consumers perceive them to be hypocritical. We conducted a situational simulation experiment to explore the effect of the match between corporate hypocrisy manifestation (moral hypocrisy vs. behavioral hypocrisy) and the corporate response strategy (reactive CSR communication vs. proactive CSR communication) on consumers’ negative behaviors toward an enterprise and to test the mechanism influencing this effect. The results indicated that the interaction between the type of corporate hypocrisy and the corporate response strategy has a significant effect on consumers’ negative behaviors toward an enterprise. Consumers’ negative emotions have a mediating influence on the aforementioned effect. This study explored the response strategies of enterprises during a corporate hypocrisy crisis, classified corporate hypocrisy crises into two types (moral hypocrisy vs. behavioral hypocrisy) according to the different manifestations of corporate hypocrisy, and introduced situational crisis communication theory (SCCT) into research on corporate hypocrisy. The present results help expand knowledge on corporate hypocrisy.